2013
DOI: 10.1111/gcb.12119
|View full text |Cite
|
Sign up to set email alerts
|

Modelling as a tool for analysing the temperature‐dependent future of the Colorado potato beetle in Europe

Abstract: A warmer climate may increase the risk of attacks by insect pests on agricultural crops, and questions on how to adapt management practice have created a need for impact models. Phenological models driven by climate data can be used for assessing the potential distribution and voltinism of different insect species, but the quality of the simulations is influenced by a range of uncertainties. In this study, we model the temperature-dependent activity and development of the Colorado potato beetle, and analyse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…In changed warmer climatic conditions, new pathogens will give rise to new problems in the future (Jönsson et al, 2013). Our results confirm that potato early blight has already become a more serious problem for North-East European organic potato growers.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In changed warmer climatic conditions, new pathogens will give rise to new problems in the future (Jönsson et al, 2013). Our results confirm that potato early blight has already become a more serious problem for North-East European organic potato growers.…”
Section: Discussionsupporting
confidence: 74%
“…In recent years, early blight has occurred with increasing frequency in potato fields in northern regions, especially on fields with susceptible potato cultivars and damage has been more serious than before due to changed climate conditions (Kocmánková et al, 2010). Moreover, Jönsson et al (2013) predict further increase in warmer summers, which could cause greater problems from this pathogen in northern regions. In Latvia, Treikale et al (2008) have reported increased potato early blight damage in recent years on potatoes grown as a monoculture with a high level of nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Beetle survival does not appear to be affected by cold weather during the growing season (93). Rather, the number of generations per year increases with temperature, with each generation requiring around 400 growing degree days (>10 • C) (68,116,164). In Estonia, for example, the CPB produced a distinct second generation during 2010, perhaps for the first time since entering the country in 1965 (57).…”
Section: Climate Change and The Colorado Potato Beetlementioning
confidence: 99%
“…The temperature dependence of the CPB has motivated numerous studies on the potential effect of climate change on future distributions (68,72,116,136,159). In general, models predict an increase in the number of generations per year as the planet warms and consequently a poleward shift in the distribution in Eurasia, but results are highly sensitive to the climate model used.…”
Section: Climate Change and The Colorado Potato Beetlementioning
confidence: 99%
“…The developmental threshold has a major impact on the development and number of generations of CPB per year (Jönsson et al 2013). In Estonia, due to warm springs in some years, the beetles emerged already in early May allowing development of a second generation.…”
Section: Discussionmentioning
confidence: 99%